2008
DOI: 10.1103/physrevb.78.075428
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of small cobalt clusters on low-index surfaces of copper: Tight-binding simulations

Abstract: Vibrational properties ͑frequencies, polarizations, and lifetimes͒ of a single adatom, dimer, and trimer of Co on low-index Cu surfaces, Cu͑111͒, Cu͑001͒, and Cu͑110͒ are studied by using tight-binding second moment approximation interatomic interaction potentials. We show that structural and vibrational properties of the Co clusters strongly depend on the substrate orientation. The longest lifetimes of 1-2.5 ps have been found for high-frequency z-polarized vibrations in all the Co clusters considered. The sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…As will be shown in the following, the spectrum experimentally recorded on a clean and topographically flat terrace using a copper terminated tip clearly indicates that features characteristic of the lattice dynamics of a clean Cu͑111͒ surface 19,20 are superimposed to phonon modes typical of small metal clusters. This copper surface is an ideal system to study the influence of the tip as the phonon spectrum of the surface is featureless in the low-energy range where the metal clusters show characteristic vibrational modes.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…As will be shown in the following, the spectrum experimentally recorded on a clean and topographically flat terrace using a copper terminated tip clearly indicates that features characteristic of the lattice dynamics of a clean Cu͑111͒ surface 19,20 are superimposed to phonon modes typical of small metal clusters. This copper surface is an ideal system to study the influence of the tip as the phonon spectrum of the surface is featureless in the low-energy range where the metal clusters show characteristic vibrational modes.…”
mentioning
confidence: 73%
“…As low-energy inelastic excitations are characteristic of small clusters of atoms, 20 the vibrational spectrum of a single copper atom adsorbed onto the Cu͑111͒ surface, as schematically drawn in the upper part of panel ͑b͒, has been calculated. The predicted vibration spectrum projected as in-plane and out-of-plane lattice displacement is shown in Fig.…”
mentioning
confidence: 99%
“…For instance, 174 (out of a total number of 180) vibration modes of C 60 exhibit energies exceeding 25 meV and are thus higher than typical metal phonon energies. In contrast, the single metal adatom have vibrational energies 90 that match the phonon energies of the electrodes. As a consequence, heat dissipation to the substrate is more effective for the adatom than for the molecule, which may explain the lower effective temperature of the adatom.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, we can suggest that Co is rejected from the Cu core and forms islands or a shell of the bcc Cu particles. It should be noted that the experimental [67] and theoretical [68,69] studies also demonstrated the formation of compact Co clusters or islands on the fcc Cu surfaces.…”
Section: Cobalt Segregationmentioning
confidence: 93%